2013
DOI: 10.4103/2230-8210.107858
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of polycystic ovary syndrome in Indian women

Abstract: Background:Polycystic ovary syndrome (PCOS) is common diagnosis in women presenting with infertility. All the dimensions of PCOS have not been completely explored. Many studies have tried to characterize the exact presentation of the disease. In this study we studied clinical features of PCOS in Indian women to characterize different phenotypes of this syndrome. Prevalence of acanthosis nigricans (AN) as surrogate marker of insulin resistance, obesity, hirsutism and hypothyroidism in PCOS women have been simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
90
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(104 citation statements)
references
References 19 publications
8
90
6
Order By: Relevance
“…Ramanand et al did a study on clinical characteristics of PCOS in Indian women and reported menstrual irregularities as the chief complaint in 100% of women, 44.16% patients showed presence of acanthosis nigricans and 44.16% women had hirsutism. 13 Antral follicles count is a potentially useful predictor of the outcome of ovarian stimulation in PCOS women. 14 Kandil et al did a study on sonographic assessment of ovarian reserve before and after laparoscopic ovarian drilling in PCOS and reported pre-treatment mean antral follicles count in LOD group was 16.5±1.3.…”
Section: Resultsmentioning
confidence: 99%
“…Ramanand et al did a study on clinical characteristics of PCOS in Indian women and reported menstrual irregularities as the chief complaint in 100% of women, 44.16% patients showed presence of acanthosis nigricans and 44.16% women had hirsutism. 13 Antral follicles count is a potentially useful predictor of the outcome of ovarian stimulation in PCOS women. 14 Kandil et al did a study on sonographic assessment of ovarian reserve before and after laparoscopic ovarian drilling in PCOS and reported pre-treatment mean antral follicles count in LOD group was 16.5±1.3.…”
Section: Resultsmentioning
confidence: 99%
“…Another study by Ramanand et al is also in concordance with our observations. 8 He observed that irregular cycles in 100% of their study participants, whereas infertility was present in 21%. Another study from Jammu and Kashmir observed menstrual disturbances in 65% of the PCOS women, whereas 35% of the patients had normal menstrual cycles.…”
Section: Discussionmentioning
confidence: 99%
“…1,7 The prevalence of metabolic disorders in women with PCOS is higher than in the healthy population, with type 2 diabetes occurring at the highest frequency (3-7 times), especially in Indians. 2,44 Other frequent disorders include hirsutism (85-90%) symptoms of metabolic syndrome (MS, approximately 40%), obesity/ overweight (40-60%), lipid disorders, arterial hypertension (approximately 20%) ( Table 1). It is worth noting that any excessive weight in these patients impairs the regularity of menstrual bleeding and responses to metformin and insulin treatment, exacerbates the symptoms of hyperandrogenism and also increases cardiovascular risk (Fig.…”
Section: Discussionmentioning
confidence: 99%